When Popular Isn't Profitable: A Menu Engineering Analysis of an Indian Fine Dining Restaurant in Jakarta - Bimo Kuncoro Jati; Shafa Radiva Assyam; Erris Kusumawidjaya; Rr Christiana Mayang Anggraeni Stj; Kezia Elsty (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study examines the classification and strategic positioning of main course menu items at Man Aur Tan Authentic Indian Cuisine Restaurant, an Indian specialty outlet on the 36th floor of Hotel Manhattan Jakarta. Using a quantitative descriptive design, the study applies the Kasavana and Smith menu engineering matrix to all 24 main course items, drawing on one month of secondary sales data to calculate contribution margin and menu mix percentage against category benchmarks. Results show only two items, Gosht Kofta and Rogan Josh Kashmiri, qualify as Stars, while thirteen items, 54.2 percent of the menu and 69.8 percent of volume, fall into the Plowhorse quadrant, generating a lower 62.9 percent share of contribution margin. Seven items, including Jheenga Jhalfezi and Jheenga Kalimirchi, are classified as Puzzles, carrying the highest per portion margins despite limited popularity, and two items are classified as Dogs. These findings indicate the restaurant's most ordered dishes are not its most profitable, pointing to unrealized margin on high volume items and untapped potential in high margin, low visibility dishes. The study recommends cost adjustments for Plowhorse items, promotional repositioning for Puzzle items, and a critical review of Dog items' place on the menu.